KAJIAN PREFERENSI UMKM DAN IKM KOTA SEMARANG TERHADAP PERDAGANGAN ONLINE - Sunyoto Sunyoto; Farid Ahmadi; Anindya Ardiansari; Ghanis Putra Widhanarto (Jurnal Riptek, 2019)
This study aims to determine the preferences of (Micro, Small and Medium Enterprises-MSMEs and Small and Medium industries-SMIs) in the city of Semarang on online trade and their impact on business development, obstacles encountered, and how the strategies of SMEs and SMIs in dealing with online trade in Semarang. The study population was MSMEs and SMIs which were spread out in 11 clusters in Semarang City and the samples were determined by purposive sampling. Data were collected using a questionnaire technique and interviews were analyzed descriptively-qualitatively. The results showed that the preference of MSMEs / SMIs in the City of Semarang towards online trade in the City of Semarang was under development. Quantitatively, there are more trade players who like the offline system (60%) compared to traders who prefer purely online (10%). However, there are relatively many business people who like to trade offline or online, which is 30%. The impact of online trade on the development of MSMEs in the city of Semarang tends to be positive, this is indicated by the research data which states that it is very profitable and profitable if the amount is 45%, and which states that it is less profitable or very unprofitable if it is only 3%. Most of the obstacles faced by MSMEs in Semarang City (84%) came from subjective and internal assessments of MSMEs in Semarang City. This is based on research findings which reveal that the constraints faced are dominated by the notion that online trading is complicated (32%), unfamiliar (29%), and there is no time (23%). Constraints due to safety factors are only 5% and other 11%. The strategies undertaken by MSMEs / SMIs actors in dealing with online trade are by improving and maintaining service quality and product quality, as well as optimization in promotions supported by new innovations.